Examining the role of emo-sensory intelligence in teaching burnout, teaching interest, and teachers' success - Reza Pishghadam; Shima Ebrahimi; Zahra Jahani (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Given the importance of teaching quality in the education of students, especially adolescents in the critical stage of identity formation, emotions arising from sensory experiences play a significant role in teaching quality, such as enthusiasm for teaching, burnout, and teaching effectiveness. The authors measured 315 (136 male and 179 female) middle school teachers’ emo-sensory intelligence (ESQ). The relationship between ESQ, the measurement of experienced burnout, teachers' success, and interest scales were also examined. Based on the descriptive and inferential analyses, burnout negatively correlated with teachers’ ESQ, success, and interest. Furthermore, mediated by burnout, ESQ positively predicted teachers’ success and interest. Teachers’ burnout negatively predicted their success and interest. Considering the correlation between ESQ, burnout, and the mediating role of burnout on success and interest, it is recommended that teachers cultivate an understanding of the ESQ concept and develop an awareness of sensory-induced emotions, which may lead to a decrease in burnout and an increase in success and interest.